Application Of Pair Share Think Learning Model To Improve Critical Thinking Ability In Social Science - Tietien Harfuthien (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2019)
The purpose of this study is to describe how to improve social science critical thinking skills by applying Think Pair Share learning model. This study uses a classroom action research method. The subjects of this study were class VIIIA students of SMP Negeri 2 Gresik totaling 32 students. The study used three research instruments, namely tests, observations and interviews. Based on the results of observations, obtained data that the highest average social sciencecritical thinking skills of students in the first cycle is 60% and the lowest is 25%. While the second cycle increased, the highest average student's social science critical thinking ability became 90% and the lowest 70%. From these results it can be concluded that the application of the think pair share learning model can improve the critical thinking skills of social science grade VIIIA students of SMP Negeri 2 Gresik. Keywords: Social Science, Critical thinking skills, Think pair share learning models